2016
DOI: 10.1038/srep36289
|View full text |Cite
|
Sign up to set email alerts
|

Oncometabolite D-2-Hydroxyglurate Directly Induces Epithelial-Mesenchymal Transition and is Associated with Distant Metastasis in Colorectal Cancer

Abstract: Deranged metabolism is a hallmark of cancer, playing a significant role in driving the disease process. One such example is the induction of carcinogenesis by the oncometabolite D-2 hydroxyglutarate (D-2HG), which is produced by the mutated enzyme isocitrate dehydrogenase (IDH) occurring in subsets of leukaemias and brain tumours. The oncogenic property of D-2HG appears to stem from its ability to interfere with the activities of α-ketoglutarate-dependent dioxygenases, including the Jumonji family histone deme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 49 publications
1
100
0
Order By: Relevance
“…A key finding of our study is the discovery that both ADHFE1 and D-2HG similarly induce EMT, stemness, and invasion of mammary cells. It has previously been shown that mutant IDH and D-2HG promote EMT in human colon cancer cells (30,37). Similarly, accumulation of fumarate in fumarate hydratase-deficient cells induces EMT through inhibition of a Tet-mediated demethylation process in the regulatory region of the miR-200ba429 cluster (51).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A key finding of our study is the discovery that both ADHFE1 and D-2HG similarly induce EMT, stemness, and invasion of mammary cells. It has previously been shown that mutant IDH and D-2HG promote EMT in human colon cancer cells (30,37). Similarly, accumulation of fumarate in fumarate hydratase-deficient cells induces EMT through inhibition of a Tet-mediated demethylation process in the regulatory region of the miR-200ba429 cluster (51).…”
Section: Discussionmentioning
confidence: 98%
“…2HG inhibits histone lysine demethylases, which can lead to increased methylation of histones (28,29). It was shown that D-2HG increases trimethylation of histone H3 lysine 4 (H3K4me3) in the promoter region of the EMT regulator, ZEB1, in HCT116 colorectal cancer cells (30). Increased EMT.…”
Section: D-2hg Is the Predominant Enantiomer Elevated In Human Breastmentioning
confidence: 99%
See 1 more Smart Citation
“…in acute myeloid leukemia and glioblas toma [211,212], al though sig nif i cant lev els of this on cometabo lite were also de tected in colon car ci noma cell lines in de pen dently of any mu ta tion [213]. These metabo lites are able to in hibit α ke tog lu tarate de pen dent dioxy ge nases among which the afore men tioned HIF 1α neg a tive reg u la tor PHD2 [214][215][216], but also TET fam ily of 5 methyl cy to sine hy drox y lases and Ju monji fam ily of hi s tone demethy lases [217][218][219], as pre vi ously dis cussed in para graph 2.…”
Section: Metabolic Contribution To Cancer Metastasismentioning
confidence: 97%
“…These metabo lites are able to in hibit α ke tog lu tarate de pen dent dioxy ge nases among which the afore men tioned HIF 1α neg a tive reg u la tor PHD2 [214][215][216], but also TET fam ily of 5 methyl cy to sine hy drox y lases and Ju monji fam ily of hi s tone demethy lases [217][218][219], as pre vi ously dis cussed in para graph 2. In hi bi tion of the last two re sults in DNA and hi s tone hy per me thy la tion which, in turn, re presses miR 200 ex pres sion [220,221] and/ or in duces EMT re lated tran scrip tion fac tors [220], lead ing to re pres sion of ep ithe lial mark ers, ex pres sion of mes enchy mal mark ers, and ac qui si tion of mi gra tory and in va sive traits [213,220,222,223].…”
Section: Metabolic Contribution To Cancer Metastasismentioning
confidence: 99%